BENEFITS OF ORGANIC FARMING ON SOIL AND CROP HEALTH: A CASE STUDY - B Satheesh (African Journal of Environmental Economics and Management, 2025)
Organic farming system in India is not new and is being followed from ancient time. It is a method of farming system which primarily aimed at cultivating the land and raising crops in such a way, as to keep the soil alive and in good health by use of organic wastes (crop, animal and farm wastes, aquatic wastes) and other biological materials along with beneficial microbes (biofertilizers) to release nutrients to crops for increased sustainable production in an eco-friendly pollution free environment. It was observed that the regular application of vermicompost improved the pH status from acidic to normal. Initially the majority of the soil samples were deficient in organic carbon, nitrogen, phosphorous and potassium, the application of vermicompost over a period of three year improved the fertility status to sufficient.